Inclusion, Disability and Culture - Hassanein, Elsayed Elshabrawy Ahmad. (Studies in Inclusive Education, 2015)
This book examines some theoretical and empirical aspects about complexities of inclusion, disability and culture. It challenges the globalized technical and reductionist approach of inclusion and argues that concepts of disability and inclusion are culturally constructed. Disability and inclusion are concepts which do not define a global agenda, in the sense that one size fits all. Rather they should be seen as being completely context dependent and that they should be deconstructed with respect to specific cultural contexts, with respects to society, ethics, religion and history. The main argument of the book is that many cultural backgrounds, including Egyptians, have their own long-standing beliefs and practices which do not define or address disability in the same way as western culture. Such cultural differences in understanding disability may lead to different understandings, conceptualizations and practices of inclusion. The book articulates disability and inclusion within a socio-ethical-religious discourse based on the Islamic underpinnings of equality and differences. This discourse enhances and supports the calls for considering inclusion and disability within a cultural model that takes into account the common values about disability in any given context which consequently will affect the way educational provision is provided in that context. Finally, the book challenges the “psychological” concept of “attitude” that has been represented in the literature simply as a matter of acceptance or rejection. Inclusion, Disability and Culture shows that “attitude” is a complex and context-dependent issue that can’t be understood in isolation from the wider context within which such responses were created. Specifically, the role of the social views about disability, religious values, school cultures, educational system and structural and organizational constraints can’t be underestimated in understanding teachers’ attitudes towards a complex issue like inclusion.